The influence of grafted cellulose nanofibers and postextrusion annealing treatment on selected properties of poly(lactic acid) filaments for 3D printing. Issue 11 (3rd April 2017) - Dong, Ju; Li, Meichun; Zhou, Ling; Lee, Sunyoung; Mei, Changtong; Xu, Xinwu; Wu, Qinglin
ABSTRACT: l ‐lactide monomers were grafted onto cellulose nanofibers (CNFs) via ring‐opening polymerization, forming poly(lactic acid) grafted cellulose nanofibers (PLA‐ g ‐CNFs). PLA‐ g ‐CNFs and pristine PLA were then blended in chloroform and dried to prepare a master batch. PLA‐ g ‐CNFs/PLA composite filaments targeted for 3D printing were produced by compounding the master batch in PLA matrix and melt extrusion. The as‐extruded composite filaments were subsequently thermal annealed in a conventional oven, and their morphological, thermal, and mechanical properties were evaluated. PLA was successfully grafted on the surface of CNFs as demonstrated by elemental analysis, and the concentration of grafted PLA was estimated to be 33 wt %. The grafted PLA were highly crystallized, contributing to the growth of crystalline regions of PLA matrix. The incorporation of PLA‐ g ‐CNFs improved storage modulus of the composite filaments in both low temperature glassy state and high temperature rubbery state. Postextrusion annealing treatment led to 28 and 63% increases for tensile modulus and strength of the filaments, respectively. Simulated Young's moduli from the Halpin‐Tsai and Krenchel models were found comparable with the experimental values. The formed composite filaments are suitable for use in 3D printing. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 847–855 Abstract : Poly(lactic acid) grafted cellulose nanofibers (PLA‐ g ‐CNFs) were synthesized via ring‐opening polymerization and were subsequently used to strengthen PLA‐based filaments for 3D printing. The incorporation of PLA‐ g ‐CNFs combined with post extrusion annealing treatment improved the storage modulus of the composite filaments in both low temperature glassy state and high temperature rubbery state. The processed filaments showed 28 and 63% increases in tensile modulus and strength, respectively.